E-health services and their requirements evaluation - Stašys, Rimantas (Business, Management and Economics Engineering, 2010)
E-health could be defined as the use of modern information technologies within the health care facilities in order to better satisfy expectations and needs of the patients, medical staff and administration. As the research shows economic profits exceed investments in the e-health three times. Studies in Lithuania in December of 2008 show that only 38% of the country hospitals have online WebPages. Only large hospitals located in the major Lithuanian cities have internet sites. Situation within the outpatient facilities is even worse. Only 12% of these health care facilities had online services offered to the public according to the survey completed at the end of 2008. There is insufficient focus for doctors’ advices and not enough links to other websites. Additionally, many sites do not contain information about career opportunities within a facility. Finally, online sites lack such information as the institution’s service charges or their implementation for various projects. Only a few hospitals have an online registra-tion feature and very few provide work hours. Outpatient service facilities do not reflect the institution’s activities adequately. None of the outpatient service facilities provide business reports; there is no information about their participation in the international projects. Only four WebPages contain sections providing the career opportunities for the office and a list of new doctor positions available. By the comparison of the Webpages of polyclinics and health care facilities one can indicate that polyclinic facilities have better online pages. Most of the health care consumers would use the Internet to find out such information as the doctor’s qualifications and work experience, information about main diseases and their symptoms, the medications and their side effects, tips on healthy lifestyle, as well as utilize registration to a specialist feature. Most of the respondents surveyed also indicated that there should be more information about health care services and their prices, institution’s medical equipment and devices as well as their methods of treatment. The best practice for the e-Health website is classifying it into four groups: information on the health care institution, information relating to the services provided, information on the medical staff working in the office, other information. 48% of the respondents were not familiar with the online registration possibility, and 74% of survey participants would like to use the feature. Only 13% of the respondents knew that they could fill prescription online and only 10% were aware of the electronic medical record. All of this leads to the conclusion that Lithuanian consumers lack information about the e-health.Article in Lithuanian.Elektroninės sveikatos paslaugos ir jų poreikio vertinimas